Students' Difficulty in Solving Math Problems Material Volume Build Room SDN Pedurungan Kidul 01 - Martha, Thoyib (Fakultas Ilmu Pendidikan, Universitas Persatuan Guru Republik Indonesia Semarang, 2021)
Solving math problems begins with understanding the problem itself. The purpose of this study was to find out what difficulties students experience in solving math problems. This type of research is descriptive qualitative. Using test, observation, interview, questionnaire and documentation methods. The subjects of this study were students of class VB SDN Pedurungan Kidul 01 Semarang. The results of this study were students in class VB experienced student difficulties in understanding the problem, changing units and difficulties in counting and the factors that influenced the difficulty of students in solving mathematics problems in the volume of space building materials, including student and teacher factors.